'We're not useless, we know stuff!' Gathering children's voices to inform policy. Issue 2 (June 2023) - Barblett, Lennie; Bobongie-Harris, Francis; Cartmel, Jennifer; Hadley, Fay; Harrison, Linda; Irvine, Susan; Lavina, Leanne
'We're not useless, we know stuff!', said a four-year-old when asked why adults should ask him what he thinks about his experiences at his early learning centre. This paper describes the literature and methods used to gather children's voices in early childhood and education (ECEC) settings across Stage 1 and 2 of the 3 stage national Learning Frameworks Update project. Asking children about their ideas and experiences was undertaken by familiar educators using research tools designed and supported by the research team. The methods of dialogic drawing, talking circles and visual elicitation were described and further explained to enable educators to gather children's perspectives on their learning experiences in ECEC contexts. We reflect on the efficacy of these methods, approaches and strategies to support meaning-making from a diverse representation of children and how this can influence policy decision-making.